Archipelago : A Novel - Roffey, Monique (London Simon & Schuster, 2013)
When a flood destroys Gavin Weald's home, tearing apart his family and his way of life, he doesn't know how to continue. A year later, he returns to his rebuilt home and tries to start again, but when the new rainy season arrives, so do his daughter's nightmares about the torrents, and life there becomes unbearable. So father and daughter - and their dog - embark upon a voyage to make peace with the waters. Their journey will take them far from their Caribbean island home, into other unknown harbours and eventually across a massive ocean. They will sail through archipelagos, encounter the grandeur of the sea, meet with the challenges and surprises of the natural world. A miraculous future lies ahead of them, unknown territories await to be discovered. But it will take more than an ocean to put the memory of the flood behind them.
Keywords: Fathers and Daughters -- Sea Stories -- Floods